Intelligent Robotics and Applications 6th International Conference, ICIRA 2013, Busan, South Korea, September 25-28, 2013, Proceedings, Part I - Lee, Jangmyung; Lee, Min Cheol; Liu, Honghai; Ryu, Jee-Hwan (Lecture Notes in Artificial Intelligence,, 2013)
This two volumes set LNAI 8102 and LNAI 8103 constitutes the refereed proceedings of the 6th International Conference on Intelligent Robotics and Applications, ICIRA 2013, held in Busan, South Korea, in September 2013. The 147 revised full papers presented were carefully reviewed and selected from 184 submissions. The papers discuss various topics from intelligent robotics, automation and mechatronics with particular emphasis on technical challenges associated with varied applications such as biomedical application, industrial automation, surveillance and sustainable mobility.